Analysing address forms in openings and closings in nurse-patient communication / Thinusha A/P Selvaraj - Thinusha, Selvaraj (2013)
is important to have good and effective communication between nurses and patients. There are many ways to start and end a conversation. It is said that openings in the form of greetings and a proper closing is needed in a conversation to maintain a cordial relationship between speakers. Therefore the objectives of this study are to identify the forms of addresses used by nurses when communicating with their patients and the relationships between the forms of addresses used and the language choice in the nurse-patient communication. It is important to know the terms of address used because this use determines solidarity among the speakers. The literature review reveals aspects of nurse-patient conversation such as communication, information, collaboration, forms of addresses in openings and closings of a conversation and language accommodation in using the address forms. The data for this study has been taken from surveys and observations. Observations and surveys were conducted among randomly selected nurses from East Tower of University Malaya Medical Centre (UMMC). The quantitative analysis of the data revealed many types of address forms used by the nurses when communicating with their patients. The findings of quantitative analysis also showed the choice of languages the nurses used when communicating with patients from different ethnic groups. The discourse analysis revealed the intention of using address forms in communication and how the language accommodates communication when conversation across cultures took place. A summary of the entire research is presented in Chapter five. The study is significance for programmes or trainings developed for nurses where the nurses can be well-trained to communicate effectively instead of just being a skilled-nurse